Rigid plastic approximation to predict plastic motion under strong earthquakes. - Paglietti, A. (Earthquake engineering & structural dynamics.)
The paper shows that the rigid plastic oscillator can be used to evaluate the maximum plastic displacement of any elastic plastic oscillator under any earthquake. Motivated by this result a rigid plastic response spectrum is introduced, which provides an easy method to calculate the maximum plastic displacement of a rigid plastic oscillator for any given earthquake. Such a spectrum is easier to construct than the elastic plastic response spectrum or the classical elastic one. By means of appropriate formulas presented in the paper, the rigid plastic response spectrum can be used to determine a realistic upper bound to the maximum plastic displacement of any elastic plastic oscillator under the given earthquake.